THE RELEVANCE, ACHIEVEMENTS AND CHALLENGES OF WOMEN'S PARTICIPATION IN STEM IN UZBEKISTAN ANALYSIS AND CONCLUSIONS - Nargiza Maxsatjonovna Xasanova (Web of Journals Publishing, 2025)
The article analyzes the importance of women's active participation in science and technology, especially in STEM (Science, Technology, Engineering, and Mathematics), the state policies and initiatives being implemented in this regard, the achievements and challenges in ensuring gender equality in each area, as well as the impact of women's participation in science on the socio-economic development of society.
Keywords: Science, technology, women, gender equality, scientific development, STEM, socio-economic policy, innovations, technological progress, scientific discoveries, grants, involvement in science, technological achievements.